2010
DOI: 10.1530/eje-09-0509
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, management and therapeutic outcome in prepubertal Cushing's disease

Abstract: Objectives: Cushing's disease (CD) in prepubertal children is very rare and presents important diagnostic and therapeutic challenges. We report experience of the management of this subpopulation of CD patients. Study design/methods: Retrospective patient case note review. Results: Between 1985 and 2008, 17 prepubertal children (13M, 4F), aged 5.7-14.1 years presented to our centre for diagnosis and management of CD. All children had subnormal linear growth and excessive weight gain at presentation. A high prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…The first one [30] showed that BSIPSS correctly predicted the tumour position in all (4) cases; in the second [75] and third [76] research there was concordance between the BSIPSS finding and the position of the microadenoma at surgery in, respectively, 81% (17/21) and 91% (10/11) patients. The last study reported that in 91% of patients BSIPSS showed the correct position of pituitary adenoma [70].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The first one [30] showed that BSIPSS correctly predicted the tumour position in all (4) cases; in the second [75] and third [76] research there was concordance between the BSIPSS finding and the position of the microadenoma at surgery in, respectively, 81% (17/21) and 91% (10/11) patients. The last study reported that in 91% of patients BSIPSS showed the correct position of pituitary adenoma [70].…”
Section: Reviewmentioning
confidence: 99%
“…Bilateral simultaneous inferior petrosal sinus sampling is a highly specialised technique and should be performed by experienced interventional neuroradiologists with a team of trained operators [30,69]. In the majority of cases, general anaesthesia (GA) is not required; however, in young children GA may be necessary [30,70]. In the study by Dias et al children with GA were aged 5.6 and 6.6 years, and BSIPSS, despite GA, gave valid results [70].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The earlier the state of disease the more subtle may be the signs and symptoms. Several reviews and guidelines try to help in diagnosing this disease state [2][3][4] . The accuracy and usefulness of the laboratory tests and procedures for the diagnosis of CS was also evaluated 5 .…”
Section: Editorial the Diagnosis Of Pediatric Cushing's Syndrome Is Nmentioning
confidence: 99%
“…CS in children and adolescents is estimated to comprise 10% of diagnosed cases, but population-based epidemiological data are lacking (3). As in adults, CD remains the most common cause of endogenous CS in children (85%), with a female predominance (4) (although a male predominance has been reported in prepubertal children (5,6,7). The onset of the disease is insidious, but its hallmark is obesity combined with longitudinal growth retardation (4,5).…”
Section: Introductionmentioning
confidence: 99%